COMPARATIVE STUDY BETWEEN ENGLISH AND BATAK TOBA LANGUAGE AFFIXATION IN FORMING NOUN: A MORPHOLOGICAL ANALYSIS - Manurung, Hotmaida; Johan, MHD (SCIENTIA JOURNAL, 2019)
Affixation not only found in English but also in Batak Toba Language. The affixation process is one of the morphological processes. This research aims to describe the similarities and differences between English and Batak Toba language in forming noun attached by prefix and suffix based on the form and meaning. This research is qualitative research. In the data collection the researcher uses observation (simak) method by using uninvolved conversation observation (simak bebas libat cakap) technique. The method of data analysis used by the researcher is distributional (agih) method by using expansion (perluas) technique. The method of presenting research result, the researcher uses informal methods by using sentences or words. From the analysis that has been done the researcher found the similarities and differences of affixation between English and Batak Toba language in forming noun. The differences found by researcher namely prefix in English does not change the form of word class while the prefix in Batak Toba mostly change the word class. The similarities found by researcher is suffixes in both languages mostly changing the form of word class. In the aspect of meaning both of languages convert the meaning after adding the prefix and suffix to the base word.